Explicating the challenges of providing novel media experiences driven by user personal data - Sailaja, Neelima; Crabtree, Andy; McAuley, Derek; Stenton, Phil (2018)
The turn towards personal data to drive novel media experiences has resulted in a shift in the priorities and challenges associated with media creation and dissemination. This paper takes up the challenge of explicating this novel and dynamic scenario through an interview study of employees delivering diverse personal data driven media services within a large U.K. based media organisation. The results identify a need for better interactions in the user-data-service ecosystem where trust and value are prioritised and balanced. Being legally compliant and going beyond just the mandatory to further ensure social accountability and ethical responsibility as an organisation are unpacked as methods to achieve this balance in data centric interactions. The work also presents how technology is seen and used as a solution for overcoming challenges and realising priorities to provide value while preserving trust within the personal data ecosystem.